Răspuns :
(x+y+z):3=33
x+y+z=33*3
x+y+z=99
(x+y):2=36
x+y=36*2
x+y=72
72+z=99
z=99-72
z=27
x=8*y
8y+y=72
9y=72
y=72:9
y=8
x=8*8
x=64
Sper ca te-am ajutat.
x+y+z=33*3
x+y+z=99
(x+y):2=36
x+y=36*2
x+y=72
72+z=99
z=99-72
z=27
x=8*y
8y+y=72
9y=72
y=72:9
y=8
x=8*8
x=64
Sper ca te-am ajutat.
(x+y+z):3=33
(x+y):2=36
x=8y
(x+y):2=36
x+y=72
8y+y=72
9y=72
y=8
x=8y
x=9*8
x=64
(64+8+z):3=33
72+z=99
z=99-72
z=27
(x+y):2=36
x=8y
(x+y):2=36
x+y=72
8y+y=72
9y=72
y=8
x=8y
x=9*8
x=64
(64+8+z):3=33
72+z=99
z=99-72
z=27